ECONOMIC AND SOCIAL PROBLEMS FROM THE JIU VALLEY AND THE NEED FOR DEVELOPMENT SUPPORT NETWORK FOR ELDERLY PEOPLE FROM PETROSANI - FELICIA ANDRIONI; MIHAELA CAMELIA SCHMIDT (Annals of the University of Petrosani: Economics, 2011)
This paper explores a few aspects of social and economic problems in the Jiu Valley, issues that have led to a priority need for the development of the share of social support network in this area. The needs of the population generated by economic and social problems existing in the Jiu Valley has led the development of social services in response to these needs. Also the paper contents a case study about necessity development of social support network for elderly from Petrosani area.